Investigation of photocatalytic and luminescence properties of Na0.5Ce0.5WO4 self-assembled photocatalysts under solar light irradiation: Morphological, temperature and pH role. Issue 10 (15th May 2023) - Dirany, Nadine; Chevallier, Virginie; Hajjoul, Oussam; Mounier, Stéphane; Arab, Madjid
Abstract: Tungstate-based scheelite structures have attracted much attention for the photocatalytic, adsorption and luminescence. To improve their performance, several ways have been considered, such as morphology control, thermal treatment and nanostructuring materials. In this work, three uniform and homogeneous morphologies, such as spindles, spheres and flowers, of self-assembled three-dimensional Na0.5 Ce0.5 WO4 were used as photocatalysts for methylene blue dye photodegradation under solar irradiation. Depending on morphology, they required different temperatures to reach crystallization. Thermal treatments at 500 °C and 800 °C resulted in changes in crystallite size, porosity, surface state, but also in bandgap and emission properties. Thus, the crystallite sizes are about 50 nm for samples (spindles and flowers) treated at 500°Cand 87–167 nm for those treated at 800 °C. Their respective bandgap values measured by diffuse reflectance were 2.85 eV beyond 3.15 eV. The samples treated at 500 °C showed a lower emission and a longer charge carrier lifetime. A strong trend to adsorption was revealed, especially at low pH value and for the samples treated at 500 °C, reaching 100% at a pH value of 2.5. With decreasing pH, the photocatalysis activity increases (up to 50%), being also more efficient with catalysts treated at low temperature. It follows that the degradation efficiency of spindles treated at 500 °C is clearly higher compared to other morphologies treated at different temperature, and suitable for solar photocatalysis.